PHYSICAL FUNCTION AFTER RESISTANCE TRAINING AMONG OLD ADULTS WITH METABOLIC SYNDROME. (11th November 2018) - Ramel, A; Geirsdottir, O; Chang, M; Jonsson, P; Thorsdottir, I
Abstract: Metabolic dysregulation affects physical performance among older adults. Metabolic syndrome (MetS) is an index of collected risk factors for cardiovascular disease/diabetes and the prevalence of MetS increases with aging. However, there is little information for the longitudinal association between MetS and physical function. We investigated the effects of a 12-week resistance exercise programme on physical function among community dwelling old adults with and without MetS. Total 236 subjects (73.7 ± 5.7 years, 58.2% female) participated in the exercise intervention and 210 people completed the program. MetS was defined according to the NIH criteria (having ≥three risk factors, i.e., increased waist circumference, triglycerides, HDL cholesterol, blood pressure, fasting glucose). Objectively measured physical function included 6-minutes-walk-for-distance (6MWD), grip strength, timed-up-and-og (TUG) and knee extension strength. The prevalence of MetS was 33% (n=78). The improvement of 6MWD from baseline to endpoint was 39.0 ± 33.2 meter for people without MetS, and 22.1 ± 35.5 meter for people with MetS. The linear regression model was performed to examine the association between baseline MetS and improvement of each physical performance after the intervention. Compared with those without MetS, those with MetS improved significantly less in 6MWD (β=-14.6, 95% Confidence interval; -26.5 to -2.7, P <0.017) after adjusting for age, gender, physical activity and body mass index, and cognitive function, but no significant difference was found in other physical function. In conclusion, older adults with MetS improved significantly less in mobility function compared with those without MetS after the resistance exercise.